Analisis Implementasi Pembelajaran Berbasis Neurosciencie - Yeni Alfina; Masduki Asbari; Siti Habibah (AGUSPATI RESEARCH INSTITUTA, 2024)
This research aims to find out the concept of Mr. Munif Chatib's thoughts about learning and education. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to oral narratives from the Risal Tv YouTube channel delivered by Mr. Munif Chatib entitled